Resilience attenuates the association between neurocognitive functioning and everyday functioning in individuals aging with HIV in the Deep South. (19th September 2018) - Fazeli, Pariya L.; Moore, Raeanne C.; Vance, David E.
Abstract : Objectives: Adults aging with HIV are at risk for poorer neurocognitive and daily functioning. Identifying factors to protect such outcomes is a significant research priority. The aim of this study was to explore the role of resilience in cognitive and everyday functioning in a largely African American and low socioeconomic status sample of adults and older adults with HIV in the Deep South. Methods/Design: In this cross‐sectional study 100 HIV+ middle‐aged and older adults (range 40‐73; 61% aged 50+) completed a comprehensive neurocognitive battery along with self‐reported measures of resilience and everyday functioning. Results: Higher resilience was associated with better global neurocognitive functioning (rho = 0.31, P  < 0.01), as well as better functioning in all domains (verbal fluency, executive functioning, speed of information processing, learning, working memory) except recall and motor skills. Resilience was also significantly associated with instrumental activities of daily living (IADL) dependence, with lower resilience observed in those with IADL dependence compared with those who were IADL independent ( P  < 0.01). In a multiple regression adjusting for data‐driven covariates (verbal IQ, income, depression), and global neurocognitive impairment, resilience was the only significant ( P  = 0.02) correlate of IADL dependence. A follow‐up mediation showed that the direct relationship between neurocognitive functioning and IADL declines was fully attenuated after accounting for shared variance with resilience. Conclusions: Resilience is associated with better cognitive and functional outcomes in people aging with HIV. While further work is needed to understand these associations over time, results suggest interventions to build resilience may promote successful aging in this vulnerable population.